Career Adaptability on Transferred Employees: The Role of Emotional Intelligence - Allya Roosallyn Assyofa; Adiva Rahmah Cintantya; Affandi Iss; Azzahra Nurul Hidayah (Applied Quantitative Analysis, 2025)
Career transitions, such as job transfers, present significant psychological and professional challenges for employees. A person’s career adaptability, which encompasses concern, control, curiosity, and confidence in managing career transitions, is crucial for sustaining performance and well-being in dynamic work environments. Emotional intelligence (EI) has been highlighted as an important aspect in allowing successful adaption during such shifts, as it enhances individuals' capacity for flexibility and self-regulation—core components of career adaptability. is described as the ability to notice, analyze, manage, and regulate emotions. Numerous studies have explored EI and career adaptability separately; limited research has specifically examined their relationship within the context of transferred employees. This study investigates the impact of EI on career adaptability among transferred employees—individuals who often face significant professional and psychological adjustments due to organizational relocation or role changes among employees of the West Java & Banten Regional Division of Perum Perhutani. Employing a quantitative approach with descriptive and verification analysis, data were collected from 77 transferred employees using structured questionnaires. EI was measured using Goleman's EI Theory, while career adaptability was tested using Savickas' Career Adapt-Abilities Scale. Statistical analysis was conducted using SPSS 22.0. The results indicate that both EI and career adaptability levels are generally high among participants, with average scores of 82.4% and 82.9%, respectively. Regression study shows a moderate but statistically significant positive connection between EI and career adaptability, with EI accounts for 69.8% of the variance in career adaptability. These findings emphasize the significance of developing EI as a strategic asset in enabling employee transitions and improving adaptive career behaviors.